Performance-based building codes: a call for injury prevention indicators that bridge health and building sectors. Issue 5 (3rd October 2008) - Edwards, N
Abstract : The international introduction of performance-based building codes calls for a re-examination of indicators used to monitor their implementation. Indicators used in the building sector have a business orientation, target the life cycle of buildings, and guide asset management. In contrast, indicators used in the health sector focus on injury prevention, have a behavioural orientation, lack specificity with respect to features of the built environment, and do not take into account patterns of building use or building longevity. Suggestions for metrics that bridge the building and health sectors are discussed. The need for integrated surveillance systems in health and building sectors is outlined. It is time to reconsider commonly used epidemiological indicators in the field of injury prevention and determine their utility to address the accountability requirements of performance-based codes.